2017
DOI: 10.5005/jp-journals-10016-1141
|View full text |Cite
|
Sign up to set email alerts
|

Does Weight Loss improve Fertility with respect to Semen Parameters—Results from a Large Cohort Study

Abstract: Objective To determine whether weight loss in obese men improves seminal parameters. Design Prospective interventional study. Setting Infertility clinic and weight loss centers. Patient All men attending infertility center and weight loss programmes from April 2012 to May 2015 (n = 105). Intervention Diet counseling and exercise. Main Outcome Measure Collected reproductive parameters included semen analysis (ejaculate volume, sperm concentration, progressive and non-progressive motility) data. Body m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…115 Therefore additional studies are needed to draw strong conclusions in this area. 56,116,117 It is noteworthy that the extent to which semen parameter improvements associated with weight loss are accompanied by concomitant improvements in reproductive potential need to be further studied because most infertile men have normal sperm quality. However, considering the increasing prevalence of obesity and decreasing male fertility, it is suggested that clinicians should have increased awareness of the effects of obesity on fertility and the underlying mechanisms in order to appropriately counsel patients and provide more effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…115 Therefore additional studies are needed to draw strong conclusions in this area. 56,116,117 It is noteworthy that the extent to which semen parameter improvements associated with weight loss are accompanied by concomitant improvements in reproductive potential need to be further studied because most infertile men have normal sperm quality. However, considering the increasing prevalence of obesity and decreasing male fertility, it is suggested that clinicians should have increased awareness of the effects of obesity on fertility and the underlying mechanisms in order to appropriately counsel patients and provide more effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Jaffar, in 2016, showed that weight loss had significant positive correlation with the percentage of progressive motile sperm and percentage of static sperm. [25] A recent meta-analysis by Macdonald et al suggested that no association exists between BMI and seminal parameters. [26] Aghamohammadi et al, in 2014, concluded that there was no statistical correlation between BMI and sperm concentration, sperm motility, sperm morphology, or ejaculate volume.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they found that testosterone treatment significantly attenuates inflammation progression, mediated by blocking the infiltration of inflammatory immune cells and promoting the expansion of competent CD4 + CD25 + Foxp3 + Tregs in testes (71,192,193). Furthermore, aromatase inhibitors increase testosterone in obese males and improve spermatogenesis and sperm quality; however, significant evidence-based studies on the management of male fertility remain lacking (182). Although the adequate concentration of testosterone is critical for spermatogenesis, excessive testosterone through testosterone therapy generally deteriorates fertility parameters in males via the negative feedback mechanism and should not be used as part of fertility management (182,194).…”
Section: Hormone Therapymentioning
confidence: 99%